2023
DOI: 10.1002/alz.13095
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific declines in cholinergic‐targeting tRNA fragments in the nucleus accumbens in Alzheimer's disease

Abstract: IntroductionFemales with Alzheimer's disease (AD) suffer accelerated dementia and loss of cholinergic neurons compared to males, but the underlying mechanisms are unknown. Seeking causal contributors to both these phenomena, we pursued changes in transfer RNS (tRNA) fragments (tRFs) targeting cholinergic transcripts (CholinotRFs).MethodsWe analyzed small RNA‐sequencing (RNA‐Seq) data from the nucleus accumbens (NAc) brain region which is enriched in cholinergic neurons, compared to hypothalamic or cortical tis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 76 publications
0
20
1
Order By: Relevance
“…Additionally, sex‐dependent changes in transfer‐RNA‐fragments (tRFs), which are non‐coding RNA regulators, have been reported in AD. tRFs that modulate cholinergic transcripts in the nucleus accumbens may potentially lead to accelerated cognitive decline in females with AD 57 . Furthermore, sex hormones influence numerous neural/behavioral functions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, sex‐dependent changes in transfer‐RNA‐fragments (tRFs), which are non‐coding RNA regulators, have been reported in AD. tRFs that modulate cholinergic transcripts in the nucleus accumbens may potentially lead to accelerated cognitive decline in females with AD 57 . Furthermore, sex hormones influence numerous neural/behavioral functions.…”
Section: Discussionmentioning
confidence: 99%
“…Considering our recent findings of cognition-related female-specific AD declines of tRF regulators of cholinergic mRNAs 24 , this suggests links between Klotho-KO-induced transcriptomic perturbations to sex differences in dementia. Indeed, both miR-129-5p and miR-335-5p are also altered in the Nucleus Accumbens of female AD patients, compared to controls with no cognitive impairment 16 (Fig. 2J; Supplementary Table 5), and with the same direction of change in human AD and murine Klotho KO brains.…”
Section: Introductionmentioning
confidence: 86%
“…I) Log 2 (CPM) counts of hsa-miR-129-5p and hsa-miR-335-5p in AD paPents’ CSF and cogniPvely healthy controls, divided by sex 36 (**: p adj <0.01). J) Log 2 (CPM) counts of hsa-miR-129-5p and hsa-miR-335-5p in the Nucleus Accumbens of AD paPents (cogdx=4), compared to cogniPvely healthy individuals (cogdx=1), divided by sex 16 (**: p adj <0.01).…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61][62][63] An intriguing recent study revealed the contribution of cholinergic targeting tRFs in the nucleus accumbens to the phenomenon of accelerated dementia and cholinergic neuron loss in female AD patients, suggesting the potential of sex-adjusted anticholinesterase therapy in the treatment of AD. 64 As mentioned above, chemical modifications regulate the production of tsRNAs and are involved in the stress response. Zhang et al measured small RNA modification profiles in autopsy samples of prefrontal cortex tissue from AD patients and controls and found that modifications in 30-40-nt fragments (with the majority of tsRNAs), compared with controls, the levels of 2′-O-methylcytidine, 2′-O-methyluridine, and 7-methylguanosine were higher in the AD group.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Numerous studies have focused on the pathogenic role of calcium dysregulation caused by RyR channel leakage in AD 59–63 . An intriguing recent study revealed the contribution of cholinergic targeting tRFs in the nucleus accumbens to the phenomenon of accelerated dementia and cholinergic neuron loss in female AD patients, suggesting the potential of sex‐adjusted anticholinesterase therapy in the treatment of AD 64 . As mentioned above, chemical modifications regulate the production of tsRNAs and are involved in the stress response.…”
Section: Roles Of Tsrnas In the Occurrence And Development Of Central...mentioning
confidence: 99%